Effect of addition pliek U in feed on histomorphometric of small intestine villi of broiler - Azmi Zul; . Nurliana; Ummu Balqis; Dian Masyitha (Proceedings of The Annual International Conference, Syiah Kuala University - Life Sciences & Engineering Chapter, 2012)
The aims of this research was to find the effect of pliek u on the morphometric of small intestine villi of broiler. This research was conducted at teaching farm and Pathology Laboratory, Veterinary Medicine Faculty, Syiah Kuala University, on June to November 2011. Pliek u was collected from home industry in Jangka village, Bireuen. Pliek u added in feed with concentration of 0.5%, 1%, dan 2%, that was given every day for 28 days. Complete Randomized Design (CRD) was used in this research with four treatments K0 (control), K1 (0.5% pliek u), K2(1% plieku), and K3(2% pliek u), each treatment group contain three broiler. The results showed that the concentration of addition pliek u in feed had no effect to histomorphometric of small intestine villi of broiler